1992
DOI: 10.1111/j.1440-1738.1992.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of the Tertiary Shimanto Belt, Muroto Peninsula, Shikoku, Japan

Abstract: The Shimanto accretionary complex on the Muroto Peninsula of Shikoku comprises two major units of Tertiary strata: the Murotohanto Sub-belt (Eocene-Oligocene) and the Nabae Sub-belt (Oligocene-Miocene). Both sub-belts have been affected by thermal overprints following the peak of accretion-related deformation. Palaeotemperatures for the entire Tertiary section range from -140 to 315"C, based upon mean vitrinite reflectance values of 0.9-5.0%Rm. Values of illite crystallinity index are consistent with condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Evidence presented by Osozawa (1992) and Sakaguchi (1996) suggests Paleocene subduction of the ridge between the Kula plate and either the Pacific or the North New Guinea plate, according to the particular reconstruction used. A second ridge subduction event was related to subduction of the Shikoku basin and its actively spreading ridge from c. 15 Ma (Hibbard & Karig 1990;Underwood et al 1992). The thermal history of the Shimanto belt suggests two episodes of cooling at _<70 Ma and c. 15 Ma, respectively (Tagami et al 1995), consistent with uplift following each of the ridge subduction events.…”
Section: Cretaceous-neogene Examplesmentioning
confidence: 93%
“…Evidence presented by Osozawa (1992) and Sakaguchi (1996) suggests Paleocene subduction of the ridge between the Kula plate and either the Pacific or the North New Guinea plate, according to the particular reconstruction used. A second ridge subduction event was related to subduction of the Shikoku basin and its actively spreading ridge from c. 15 Ma (Hibbard & Karig 1990;Underwood et al 1992). The thermal history of the Shimanto belt suggests two episodes of cooling at _<70 Ma and c. 15 Ma, respectively (Tagami et al 1995), consistent with uplift following each of the ridge subduction events.…”
Section: Cretaceous-neogene Examplesmentioning
confidence: 93%
“…It has also been suggested that the outcrop‐scale deformation in this region is not related to the later deformation but rather to the primary formation of the accretionary complex [ DiTullio and Byrne , ; DiTullio et al , ]. The thermal overprint increases with increasing proximity to Cape Muroto, where the gabbroic rocks and MORB‐type basalt dating from approximately 13 Ma are exposed [ Mori and Taguchi , ; Underwood et al , , ]. In the south of the Muroto Peninsula, near Sakihama, unexplained enigmatic andesitic pillow lavas are exposed (Figure ) [ Hibbard and Karig , ; Mizoguchi et al , ].…”
Section: Geology and Geophysics Of The Shimanto Belt On Shikoku Islandmentioning
confidence: 99%
“…In contrast to modern accretionary prisms, the large‐scale structures of ancient accretionary complexes formed in subduction zones, which are now often exposed at the surface, have been predominantly understood using geological information, such as sediment ages and paleotemperatures. Vitrinite reflectance, the degree of graphitization of the carbonaceous material included within terrigeneous sediments, is a strong tool that can be used to estimate maximum paleotemperatures [ Barker , ; Barker and Pawlewicz , ; Calundann et al ., ; Barker , ; Sweeney and Burnham , ], and vitrinite reflectance geothermometers have been widely used to reconstruct the tectonic evolution of on‐land accretionary complexes [e.g., Moore and Allwardt , ; Underwood and Strong , ; Sample and Moore , ; Underwood and Howell , ; Underwood et al ., ; Sakaguchi , ; Ohmori et al ., ; Kondo et al ., ].…”
Section: Introductionmentioning
confidence: 99%